Study of Clinico-Epidemiological Profile and Outcome of Poisonous Snake Bites in Children - Paudel, KM; Sharma, S (Journal of Nepal Paediatric Society, 2012)
Introduction: Snake bite poisoning in children is an emergency condition with significant mortality. It is more prevalent in Terai and Inner Terai regions of Nepal especially during monsoon season. There is no study on snake bite poisoning in this part of the country after the introduction of national snake bite management guideline in 2003. This retrospective study was conducted to evaluate the clinicoepidemiological profile, amount of anti-snake venom used and outcome of snake bites. Materials and Methods: Two hundred and forty six cases of snake bite poisoning admitted in emergency department of the hospital up to the age of 14 years, over a period of 6 years from 2004/2005 to 2009/2010 were evaluated retrospectively. Results: The study showed male predominance (57.3%) in snake bites with higher incidence of children above ten years of age (58%). The most of the poisonings (71.9%) was seen during June, July and August months which correspond to the monsoon season in Nepal. Majority of the victims had been bitten by unidentified snakes (52 %), mostly on the fingers & hands (64.6 %). Ptosis was observed in all cases of snake bite poisoning. Slightly less than 1/3rd of the children had respiratory distress needing respiratory support. Average ASV used was 18.2 vials. Case fatality rate (CFR) was quite high (28.2%) with more fatality on those with respiratory distress. Conclusion: As mortality due to snakebite poisoning and consumption of antisnake venom is not reduced by the use of the national protocol 2003, further study to evaluate alternate protocol is recommended. Key words: Case fatality rate; Envenomation; Nepal; Poisoning; Snakebite. DOI: http://dx.doi.org/10.3126/jnps.v32i1.5948 J. Nepal Paediatr. Soc. Vol.32(1) 2012 47-52